Crop-animal systems research in South-East Asia: Data collection for benchmark site characterization - Lapar, Ma. Lucila (International Livestock Research Institute, 1999)
This paper outlines some of the important reasons for performing benchmark site (BMS) characterization. The paper is intended to provide some guidelines on how to develop an effective instrument for data collection for the BMS characterization. It discusses how to determine the method of analysis, how to define the information to be collected, how to define the possible sources of information, how to determine the most appropriate data collection method for each type of source, how to develop an appropriate instrument for the data collection method chosen, and the implementation process.